Antitumor magnetic hyperthermia induced by RGD-functionalized Fe3O4 nanoparticles, in an experimental model of colorectal liver metastases - Arriortua, Oihane K.; Garaio, Eneko; Herrero de la Parte, Borja; Insausti, Maite; Lezama, Luis; Plazaola, Fernando; García, Jose Angel; Aizpurua, Jesús M.; Sagartzazu, Maialen; Irazola, Mireia; Etxebarria, Nestor; García-Alonso, Ignacio; et al. (Beilstein Journal of Nanotechnology, 2016)
This work reports important advances in the study of magnetic nanoparticles (MNPs) related to their application in different research fields such as magnetic hyperthermia. Nanotherapy based on targeted nanoparticles could become an attractive alternative to conventional oncologic treatments as it allows a local heating in tumoral surroundings without damage to healthy tissue. RGD-peptide-conjugated MNPs have been designed to specifically target αVβ3 receptor-expressing cancer cells, being bound the RGD peptides by “click chemistry” due to its selectivity and applicability. The thermal decomposition of iron metallo-organic precursors yield homogeneous Fe3O4 nanoparticles that have been properly functionalized with RGD peptides, and the preparation of magnetic fluids has been achieved. The nanoparticles were characterized by transmission electron microscopy (TEM), vibrating sample magnetometry (VSM), electron magnetic resonance (EMR) spectroscopy and magnetic hyperthermia. The nanoparticles present superparamagnetic behavior with very high magnetization values, which yield hyperthermia values above 500 W/g for magnetic fluids. These fluids have been administrated to rats, but instead of injecting MNP fluid directly into liver tumors, intravascular administration of MNPs in animals with induced colorectal tumors has been performed. Afterwards the animals were exposed to an alternating magnetic field in order to achieve hyperthermia. The evolution of an in vivo model has been described, resulting in a significant reduction in tumor viability.
Keywords: magnetite nanoparticles; magnetic hyperthermia; RGD functionalization; tumor targeting

(untitled) - Echevarria-Uraga, J. J.; García-Alonso, I.; Plazaola, F.; Insausti, M.; Etxebarria, N.; Saiz-López, A.; Fernández-Ruanova, B. (Int. J. Nanomed., 2012)

(untitled) - Gillams, A. R.; Lees, W. R. (Abdom. Imaging, 2005)

(untitled) - Gillams, A. R.; Lees, W. R. (J. Vasc. Interv. Radiol., 2008)

(untitled) - Vogl, T. J.; Zangos, S.; Eichler, K.; Yakoub, D.; Nabil, M. (Eur. Radiol., 2007)

(untitled) - Gray, B.; Van Hazel, G.; Hope, M.; Burton, M.; Moroz, P.; Anderson, J.; Gebski, V. (Ann. Oncol., 2001)

(untitled) - Hendlisz, A.; Van Den Eynde, M.; Peeters, M.; Maleux, G.; Lambert, B.; Vannoote, J.; De Keukeleire, K.; Verslype, C.; Defreyne, L.; Van Cutsem, E.; Delatte, P.; Delaunoit, T.; et al. (J. Clin. Oncol., 2010)

(untitled) - Wust, P.; Hildebrandt, B.; Sreenivasa, G.; Rau, B.; Gellermann, J.; Riess, H.; Felix, R.; Schlag, P. M. (Lancet Oncol., 2002)

(untitled) - Petryk, A. A.; Giustini, A. J.; Gottesman, R. E.; Kaufman, P. A.; Hoopes, P. J. (Int. J. Hyperthermia, 2013)

(untitled) - Orel, V.; Schevchenko, A.; Romanov, A.; Tselepi, M.; Mitrelias, T.; Barnes, C. H. W.; Burlaka, A.; Lukin, S.; Shchepotin, I. (Nanomedicine, 2015)

(untitled) - Yu, M. K.; Park, J.; Jon, J. (Theranostics, 2012)

(untitled) - Hola, K.; Markova, Z.; Zoppellaro, C.; Tucek, J.; Zboril, R. (Biotechnol. Adv., 2015)

(untitled) - Goya, G. F.; Grazu, V.; Ibarra, M. R. (Curr. Nanosci., 2008)

(untitled) - Fortin, J.-P.; Wilhelm, C.; Servais, J.; Ménager, C.; Bacri, J. C.; Gazeau, F. (J. Am. Chem. Soc., 2007)

(untitled) - Jain, R. K.; Stylianopoulos, T. (Nat. Rev. Clin. Oncol., 2010)

(untitled) - Tartaj, P.; Morales, M.; Gonzalez-Carreño, T.; Veintemillas-Verdaguer, S.; Serna, C. J. (Adv. Mater., 2011)

(untitled) - Roca, A. G.; Costo, R.; Rebolledo, A. F.; Veintemillas-Verdaguer, S.; Tartaj, P.; González-Carreño, T.; Morales, M. P.; Serna, C. J. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Ho, D.; Sun, X.; Sun, S. (Acc. Chem. Res., 2008)

(untitled) - Kumar, C. S. S. R.; Mohammad, F. (Adv. Drug Delivery Rev., 2011)

(untitled) - Marszałł, M. P. (Pharm. Res., 2011)

(untitled) - Jadhav, S. A.; Bongiovanni, R. (Adv. Mater. Lett., 2012)

(untitled) - Cabrera, L. I.; Somoza, Á.; Marco, J. F.; Serna, C. J.; Puerto Morales, M. (J. Nanopart. Res., 2011)

(untitled) - Toraya-Brown, S.; Sheen, M. R.; Zhang, P.; Chen, L.; Baird, J. R.; Demidenko, E.; Turk, M. J.; Hoopes, P. J.; Conejo-Garcia, J. R.; Fiering, S. (Nanomedicine, 2014)

(untitled) - Na, H. B.; Palui, G.; Rosenberg, J. T.; Ji, X.; Grant, S. C.; Mattoussi, H. (ACS Nano, 2012)

(untitled) - Ruoslahti, E. (Adv. Mater., 2012)

(untitled) - Arosio, D.; Manzoni, L.; Araldi, E. M. V.; Scolastico, C. (Bioconjugate Chem., 2011)

(untitled) - Zhang, F.; Huang, X.; Zhu, L.; Guo, N.; Niu, G.; Swierczewska, M.; Lee, S.; Xu, H.; Wang, A. Y.; Mohamedali, K. H.; Rosenblum, M. G.; Lu, G.; et al. (Biomaterials, 2012)

(untitled) - Ruoslahti, E. (Annu. Rev. Cell Dev. Biol., 1996)

(untitled) - Cao, Q.; Han, X.; Li, L. (J. Magn. Magn. Mater., 2011)

(untitled) - De la Fuente, J. M.; Berry, C. C.; Riehle, M. O.; Curtis, A. S. G. (Langmuir, 2006)

(untitled) - Das, M.; Bandyopadhyay, D.; Mishra, D.; Datir, S.; Dhak, P.; Jain, S.; Maiti, T. K.; Basak, A.; Pramanik, P. (Bioconjugate Chem., 2011)

(untitled) - Colombo, M.; Bianchi, A. (Molecules, 2010)

(untitled) - Kikuchi, T.; Kasuya, R.; Endo, S.; Nakamura, A.; Takai, T.; Meltzar-Nolte, N.; Tohji, K.; Balachandran, J. (J. Magn. Magn. Mater., 2011)

(untitled) - Meffre, A.; Medhaoui, B.; Kelsen, V.; Fazzini, P. F.; Carrey, J.; Lachaize, S.; Respaud, M.; Chaudret, B. (Nano Lett., 2012)

(untitled) - Xia, Y.; Xiong, Y.; Lim, B.; Skrabalak, S. E. (Angew. Chem., Int. Ed., 2009)

(untitled) - Yu, W. W.; Chang, E.; Sayes, C. M.; Drezek, R.; Colvin, V. L. (Nanotechnology, 2006)

(untitled) - Kale, S. N.; Jadhav, A. D.; Verma, S.; Koppikar, S.; Kaul-Ghanekar, R.; Dhole, S. D.; Ogale, S. B. (Nanomedicine, 2012)

(untitled) - Lin, C.-A. J.; Sperling, R. A.; Li, J. K.; Yang, T.; Li, P.-Y.; Zanella, M.; Chang, W. H.; Parak, W. J. (Small, 2008)

(untitled) - Eischens, R. P. (Acc. Chem. Res., 1972)

Introduction to Magnetic Materials - Cullity, B. (Addison-Wesley, 1972)

(untitled) - Wesselinowa, J. M.; Apostolova, I. (J. Phys.: Condens. Matter, 2007)

(untitled) - Stoner, E. C.; Wohlfarth, E. P. (Philos. Trans. R. Soc. London, A, 1948)

(untitled) - Nikiforov, V. N.; Koksharov, Yu. A.; Polyakov, S. N.; Malakho, A. P.; Volkov, A. V.; Moskvina, M. A.; Khomutov, G. B.; Irkhin, V. Yu. (J. Alloys Compd., 2013)

(untitled) - Wang, J.; Chen, Q.; Li, X.; Shi, L.; Peng, Z.; Zeng, C. (Chem. Phys. Lett., 2004)

(untitled) - Castellanos-Rubio, I.; Insausti, M.; Garaio, E.; Gil de Muro, I.; Plazaola, F.; Rojo, T.; Lezama, L. (Nanoscale, 2014)

(untitled) - Hutteman, M.; Mieog, J. S. D.; van der Vorst, J. R.; Dijkstra, J.; Kuppen, P. J. K.; van der Laan, A. M. A.; Tanke, H. J.; Kaijzel, E. L.; Que, I.; van de Velde, C. J. H.; Löwig, C. W. G. M.; Vahrmeijer, A. L. (Eur. J. Surg. Oncol., 2011)

(untitled) - Wu, Y.; Cai, W.; Chen, X. (Mol. Imaging Biol., 2006)

(untitled) - Mas-Moruno, C.; Rechenmacher, F.; Kessler, H. (Anti-Cancer Agents Med. Chem., 2010)

(untitled) - Kolosnjaj-Tabi, J.; Di Corato, R.; Lartigue, L.; Marangon, I.; Guardia, P.; Silva, A. K. A.; Luciani, N.; Clément, O.; Flaud, P.; Singh, J. V.; Decuzzi, P.; Pellegrino, T.; et al. (ACS Nano, 2014)

(untitled) - Lévy, M.; Gazeau, F.; Bacri, J.-C.; Wilhelm, C.; Devaud, M. (Phys. Rev. B: Condens. Matter Mater. Phys., 2011)

(untitled) - Kulhari, H.; Pooja, D.; Shrivastava, S.; Telukutala, S. R.; Barui, A. K.; Patra, C. R.; Naidu Vegi, G. M.; Adams, D. J.; Sistla, R. (Nanomedicine, 2015)

(untitled) - Hufschmid, R.; Arami, H.; Ferguson, R. M.; Gonzales, M.; Teeman, E.; Brush, L. N.; Browning, N. D.; Krishnan, K. M. (Nanoscale, 2015)

(untitled) - Zhang, L.; He, R.; Gu, H.-C. (Mater. Res. Bull., 2006)

(untitled) - Herranz, F.; Morales, M.; Roca, A. G.; Desco, M.; Ruiz-Cabello, J. (Chem. – Eur. J., 2008)

(untitled) - Khandhar, A. P.; Ferguson, R. M.; Simon, J. A.; Krishna, K. M. (J. Appl. Phys., 2012)

(untitled) - Khandhar, A. P.; Ferguson, R. M.; Simon, J. A.; Krishnan, K. M. (J. Biomed. Mater. Res., Part A, 2012)

(untitled) - Di Corato, R.; Quarta, A.; Piacenza, P.; Ragusa, A.; Figuerola, A.; Buosanti, R.; Cingolani, R.; Manna, L.; Pellegrino, T. (J. Mater. Chem., 2008)

(untitled) - Lallana, E.; Fernandez-Megia, E.; Riguera, R. (J. Am. Chem. Soc., 2009)

(untitled) - Gatteschi, D.; Fittipaldi, M.; Sangregorio, C.; Sorace, L. (Angew. Chem., Int. Ed., 2012)

(untitled) - Moros, M.; Pelaz, B.; López-Larrubia, P.; García-Martín, M. L.; Grazú, V.; de la Fuente, J. M. (Nanoscale, 2010)

(untitled) - Palomo, C.; Aizpurua, J. M.; Balentová, E.; Azcune, I.; Santos, J. I.; Jiménez-Barberó, J.; Cañada, J.; Miranda, J. I. (Org. Lett., 2008)

(untitled) - Garaio, E.; Collantes, J. M.; Plazaola, F.; Garcia, J. A.; Castellanos-Rubio, I. (Meas. Sci. Technol., 2014)